Pengaruh Musim Beranak Terhadap Produksi Susu Sapi Friesian Holstein (FH) di BPTSP-HMT Lembang - Kunaifi Wicaksana (Wahana Peternakan, 2019)
This research was aimed to analyze the influence of breeding season on the production of Frisian Holstein (FH) cattle milk. This research used secondary data covering milk production data of 81 lactation FH cattle and seasonal data (rainfall, temperature, humidity, and THI). The data is tabulated to yield the total data of each variable. Data obtained from each observed variables were analyzed using a t-test using the SAS program. Based on t-test, the results showed no significant effect on average milk production at rainy dan dry season during lactation periods of L1, L2, and L3. Our experiment suggested that season of calving showed no differences on milk production of FH dairy cattle during lactation periods of L1, L2, and L3. Conclusions in this research show that seasonal differences do not affect the diversity of milk production. Keywords: dry season, Friesian Holstein, milk production, rainy